Diagnostic, clinical management, and outcomes in patients with spinal dural arteriovenous fistula - Filis, Andreas; Romualdo, Sergio M. F.; Engellandt, Kay; El-Battrawy, Ibrahim; Podlesek, Dino; Juratli, Tareq A.; Eyüpoglu, Ilker Y.; Schackert, Gabriele; Hijazi, Mido Max (Frontiers in Surgery, 2024)
Background Spinal dural arteriovenous fistulas (SDAVFs) are rare spinal vascular malformations, but account for 70 to 80% of all spinal arteriovenous malformations. SDAVFs can be treated either surgically or endovascularly, with surgical treatment appearing to lead to higher closure rates. Our aim was to analyze the demographic data, diagnostic history, treatment characteristics and clinical short- and long-term outcomes. Methods The medical records of 81 patients who underwent surgical (n = 70, 86.4%) and endovascular (n = 11, 13.6%) treatment for SDAVF at a university hospital between 2002 and 2023 were retrospectively analyzed. Results SDAVF was observed more frequently in men than women (61, 75.3% vs. 20, 24.7%) with a mean age of 63.5 ± 12.7 years and a mean duration of symptoms to diagnosis of 12.0 ± 12.8 months. The most common first symptom was gait disturbance (36, 44.4%), followed by sensory disturbance (24, 29.6%). The location of the fistula point was most common in the lower thoracic region (36, 44.5%), followed by the lumbar region (23, 28.4%). Incomplete or failed occlusion of the fistula occurred in 8 patients (9.9%), with 6 patients (7.4%) undergoing further treatment either surgically or endovascularly. Treatment- or hospital-related complications were observed in 16 patients (19.8%). A single-level laminectomy was the most common approach (31, 44.3%), followed by single-level hemilaminectomy (28, 40.0%), and unilateral interlaminar fenestration (11, 15.7%). Back pain or radiculopathy was observed in 58% of patients (47/81) pre-treatment and had already decreased to 24.7% at hospital discharge (p < 0.001). No significant differences were observed in sensory disturbances (p = 0.681). The median of American Spinal Injury Association motor score (ASIA-MS) was 94 [82.5–100] at admission, 98 [86.5–100] at hospital discharge, 100 [90–100] at the first, second, and third follow-up (p = 0.019). The median modified Aminoff-Logue scale (mALS) was 5 [2–7] at admission, 3 [1–6] at hospital discharge, 2 [1–5] at the first follow-up, 2 [0.5–5] at the second follow-up and 2 [1–7] at the third follow-up (p = 0.006). Conclusions SDAVF occurs predominantly in men in the 6th decade of life and can be safely and effectively treated surgically and endovascularly, improving symptoms such as pain and motor deficits, gait disturbances as well as bowel and bladder dysfunction, but not sensory disturbances.